Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Defect-anchored confinement of Pt–In clusters via atomic layer deposition in hierarchical ZSM-5 for durable propane dehydrogenation - Jie Xu; Yi Yu; Chun Du; Yanfei Liu; Yaohui Dun; SenSen Yu; Fudong Liu; Yunsheng Dai; Rong Chen; Bin Shan (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Autogenous dentin graft material promotes bone regeneration involving OPN/CD44-mediated BMSC recruitment - Xin Deng; Jianmin Zhuo; Yanyan Yang; Ziliang Zhou; Jing Li; Rong Rong; Weihong Chen; Jiashen Chen; Siwen Yu; Siyuan Chen; Lu He; Janak Lal Pathak; et al. (Chemical Engineering Journal, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Perfluorohexane sulfonate (PFHxS)-induced energy metabolism disruption in Chlorella pyrenoidosa: Integrating physiological and transcriptomic insights - Biao Liao; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Shan Liu; Ji-Xun Chen; Liu-Yi Wei; Xiang-Rong Xu; Kefu Yu (Environmental Pollution, 2026)

Cascade of candidate spin liquids in a bilayer triangular-lattice antiferromagnet Rb2Co2(SeO3)3 - Xiaoyu Xu; Yunlong Wang; Xuejuan Gui; Jun Luo; Guijing Duan; Ke Shi; Zhaosheng Wang; Shuo Li; Huifen Ren; Chuanying Xi; Langsheng Ling; Zhanlong Wu; et al. (Science Bulletin, 2026)

Natural pyrite-enhanced co-culture system for simultaneous nitrate and ammonium removal under low C/N conditions: Mechanistic insights and real wastewater application - Kuang-di Xu; Pan He; Xiang-lin Liu; Lei Yu; Si-jia Li; Quan Wang; Rong-ping Chen; Ke Yin; Guang Guo; Wen-Jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Bioavailability, Migration, and Accumulation Characteristics of Heavy Metals in the Soil–Lotus Root System Adjacent to Highways - Qiang Hu; Rong-hua Qiu; Ren-chao Zhu; Manisha Parajuli; Si-jie Wen; Zi-yang Sun; Ai-hua Yu (International Journal of Environmental Research, 2026)

Temporin-GHaR6R Peptide Ameliorates Experimental Autoimmune Encephalomyelitis by Suppressing Microglial M1 Polarization and Mitochondrial Dynamics Dysfunction - Da-Qi Zhang; Hui-Min Xu; Jing Lu; Yu-Sheng Huang; Xiao-Li Feng; Li-Jun Chen; Wen-Jie Zhao; Rong Wang; Yingxia Zhang; Qifu Li (Probiotics and Antimicrobial Proteins, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Corrigendum to “Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide” [Food Res. Int. 230 (2026) 118574] - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying Li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

Latitudinal gradients shape adaptive divergence of tea saponin accumulation in Camellia oleifera - Danmei Yu; Liyun Feng; Suyun Zhang; Xiaohua Liu; Huan Yang; Jie Xiao; Shang Chen; Xia Dong; Li Cheng; Yao Zhao; Jun Rong; Jian Zhang (Food Bioscience, 2026)

Pilot-scale lithium recovery from desalination brine using needleless-electrospun mesoporous ion-sieve membranes - Naeem Nadzri; Yejin Liang; Yu Jie Lim; Kunli Goh; Atsushi Goto; Rong Wang (Desalination, 2026)

Commentary: the TSP-1-CD47-integrin α4β1 axis—deciphering pathogenic mechanisms and therapeutic horizons in rheumatoid arthritis - Jie Guo; Feng-yi Mai; Xin-yu Li; Yu Liu; Jing-rong Liang; Xing-long Li; Chen-guang Li (Inflammation Research, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Genome-wide identification and promoter activity analysis of fibrillin gene families in different color carrot roots - Yu-Jie Sun; Rong-Rong Zhang; Zi-Han Zhao; Xu Zhang; Xue-Feng Peng; Ya-Hui Wang; Ai-Sheng Xiong (Protoplasma, 2026)

Buffering failure of the ratio of secondary to primary phases: Risk overestimation of soil heavy metals under alkaline conditions - Yingdong Wu; Zixin Zeng; Rong Teng; Junwei Yang; Jiang Yu; Hui Sun; Siwei Deng; Pengxinyue Huang; Jie Luo; Yi Wu; Xuetao Zhao (Journal of Hazardous Materials, 2026)

Neomycin-sensitive gut bacteria-derived brassicasterol mediates the anti-obesity effects of Cordyceps militaris polysaccharide - Jie Cai; Aohuan Huang; Linghui You; Zelin Wang; Chaoyang Huang; Rong Huang; Ying li; Tingting Liang; Fen Zhang; Qingping Wu; Juan Wang; Zhenjun Zhu; et al. (Food Research International, 2026)

AI-Facilitated selenium-enriched peptides: Synthesis, bioactivity, virtual screening, and food industry potential, and future prospects - Zhi-Rui Ding; Jun-Wei Chen; Lin-Jie Xiao; Meng-Yu Gao; Jayani Chandrapala; Long Pan; Yang Lin; Hui-Rong Wang; Na Liu; Kang-Yi Zhang; Ai-Mei Liao (Food Bioscience, 2026)

Genome-wide CRISPR/Cas9 knockout screen identifies host factors essential for bovine parainfluenza virus type 3 replication - Jinyang Hao; Xiaoran Gao; Christine Light; Yuze Sun; Sha Lu; Yu Tian; Xia Gao; Yuan Su; Jie Gao; Xin Huang; Qianyi Zhang; Jinliang Wang; et al. (Science China Life Sciences, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Pyrite-driven redox modulation improves microbial tolerance to furan inhibitors in hydrogen production from lignocellulosic hydrolysates - Hao-Yu Sun; Xin Xu; Si-Jia Li; Lei Yu; Quan Wang; Rong-Ping Chen; Ke Yin; Guang Guo; Xu Sun; Yu-ting Xin; Wen-jie Xu; Gong-De Wu (Bioresource Technology, 2026)

Robust copper/mesoporous silica catalyst for efficient furfural hydrogenation to furfuryl alcohol - Xin-Yu Xiao; Jie Zhang; Rong Wang; Qi Wang; Hai-Song Li; Jing-He Yang (Biomass and Bioenergy, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Microbial community assembly driven by dissolved organic matter and sulfate induces arsenic transformation in shallow aquifers of lateritic red soil regions - Ming-Zhu Chen; Jun-Feng Wang; Jian-Ping Ouyang; Yi-Rong Deng; Mei-Ting Yang; Yu-Dian Xun; Xiao-Hui Shi; Guang-Yong Tang; Jian-Ying Mo; Han-Jie Ye; Qu-Sheng Li (Journal of Hazardous Materials, 2025)

Reversing the paradigm: Oxygen-dependent switch of nTiO₂ from promoting to suppressing ARG conjugation - Jie Yu; Xin Wang; Ya-Xin Hu; Feng-Ting Cao; Qiu-Rong Zhang; Xiang-Tong Zhou; Xiang Xiao (Journal of Hazardous Materials, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Quantifying the potential of high-performance RO membranes for seawater and hypersaline brine desalination: from module-scale modelling to experimental evaluation - Yu Jie Lim; Naeem Nadzri; Qiang Xue; Can Li; Yejin Liang; Rong Wang (Desalination, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Fermentation-derived dihydroferulic acid from Cordyceps militaris binds AKT1 to protect intestinal epithelial health - Rong Huang; Jixing Gao; Zelin Wang; Jie Cai; Zhenjun Zhu; Qingping Wu; Juan Wang; Fen Zhang; Yu Ding (Food Bioscience, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Postnatal exposure to various benzophenones at environmentally relevant levels enhances the susceptibility of mammalian testes to cyclophosphamide-induced spermatogenic stress in adulthood - Yan-Rong Gao; Ya-Jia Pu; Yu-Xin Sheng; Bin Cheng; Li-Jie Wang; Ya-Nan Tian; Jing Pu; Hui-Ming Ma; Hong-Mei Li; Hai-Ming Xu (Environmental Pollution, 2025)

Integrated Biofilm Modification and Transcriptional Analysis for Improving Fengycin Production in Bacillus amyloliquefaciens - Chun-Yang Cao; Zheng-Jie Hou; Ming-Zhu Ding; Geng-Rong Gao; Bin Qiao; Si-Yu Wei; Jing-Sheng Cheng (Probiotics and Antimicrobial Proteins, 2025)

Male and Female Parent Birds Enhance Their Reproductive Success Using Different Strategies but the Same Optimal Pathway - Ning‐Ning Sun; Bi‐Yun Jia; Rong‐Yu Xu; Li‐Fang Gao; Xue‐Fei Guo; Rang Li; Yu‐Jie Wang; Shu‐Min Wang; Bo Du (Molecular Ecology, 2025)
Parental birds exhibit diverse alternative reproductive strategies; however, the pathways by which these alternative strategies enhance the reproductive success of parents remain poorly understood. Here, we used generalised linear mixed models (GLMMs) and structural equation modelling (SEM) to analyse a long‐term dataset of multiple components of reproductive fitness in the azure‐winged magpie ( Cyanopica cyanus ), including incipient offspring number, extra‐pair fertilisation (EPF), unhatched eggs, offspring preyed on by predators and conspecific raiders and offspring that starved. GLMM results revealed significant associations between these components and the first lay date. SEM further elucidated causal relationships among female/male breeding conditions, cooperative breeding, first lay date and the positive/negative effects on female/male reproductive success. SEM results revealed that both female and male reproductive success were mainly influenced by negative effects rather than positive effects. Specifically, negative effects were largely determined by unhatched eggs for females but by female EPF frequency for males. In contrast, positive effects were predominantly determined by the incipient offspring number for both sexes. Therefore, minimising negative effects was prioritised over enhancing positive effects to achieve reproductive success in both sexes. To modulate these effects, females and males employed different strategies. However, they achieved their respective goals through a shared pathway: reducing negative effects for social bonds formed with smaller‐bodied males and enhancing positive effects for social bonds formed with larger‐bodied males. Our multivariate analysis of various aspects of avian reproduction suggests that the formation of social bonds plays a more important role than alternative reproductive strategies in determining individual reproductive success.

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Cytochrome P450-mediated biotransformation of octocrylene in Tetradesmus obliquus: Integrative insights from transcriptomics, proteomics, molecular docking, and density functional theory calculation - Jun-Jie Hu; Chang-Gui Pan; Xiang-Rong Xu; Feng-Jiao Peng; Shan Liu; Jiying Pei; Zhen-Zhu Liu; Hao Liang; Kefu Yu (Journal of Hazardous Materials, 2025)

Donor-receptor coordination mediated multiple antigens capture and transport for augmented cancer immunotherapy - Huan Liang; Qingqing Lu; Runyu Hu; Yixiao Zhang; Xing Rong; Guocan Yu; Jie Yang (Chemical Engineering Journal, 2025)

Synergistic antimicrobial effect and mechanism of enterocin Gr17 and cinnamaldehyde against Escherichia coli and Candida albicans - Wen-yu Ma; Kai-sheng Shen; Zhao Wang; Qi Liu; Xin-jie Diao; Guo-rong Liu (Archives of Microbiology, 2025)

Global synthesis on the responses of microbial- and plant-derived carbon to conservation tillage - Yalin Yu; Li Li; Jinkang Yang; Yinan Xu; Ahmad Latif Virk; Jie Zhou; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Plant and Soil, 2025)

Establishment of an efficient in vitro regeneration protocol for Dendrobium primulinum Lindl. by one-step seedling formation - Cheng-Li Liu; Jie-Mei Deng; Shun Peng; Heng-Yu Huang; Fu-Rong Xu (In Vitro Cellular & Developmental Biology - Plant, 2025)

The prognostic significance of histopathological growth patterns in liver metastases undergoing surgery: a systematic review and meta-analysis - Xiang-Yu Wang; Bo Zhang; Yin-Chen Gu; Mei Yang; Bao-Rui Tao; Rong-Quan Sun; Yi-Tong Li; Zhen-Mei Chen; Sen-Feng Ying; Chen-He Yi; Yan Geng; Rui Zhang; et al. (Clinical & Experimental Metastasis, 2025)

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Investigating the impact of TFC membrane structure and compaction on performance in hypersaline brine desalination via high-pressure reverse osmosis - Yu Jie Lim; Naeem Nadzri; Qiang Xue; Can Li; Rong Wang (Desalination, 2025)

Transitional chromitites within the Maqsad crust-mantle transition zone of the Semail ophiolite formed above the nascent forearc setting - Rong-Zhong Bo; Peng-Jie Cai; Dong-Yang Lian; Jing-Sui Yang; Sobhi Nasir; Hui-Chao Rui; Yu-Xiao Lu; Chu-Qi Cao; Ahmed E. Masoud (Lithos, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Lithium recovery from seawater desalination brines using ion-sieve electrospun nanofibrous membranes: the role of nanofiber design - Naeem Nadzri; Yu Jie Lim; Xiangjun Liao; Yejin Liang; Kunli Goh; Yuan Liao; Atsushi Goto; Rong Wang (Chemical Engineering Journal, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Thin-film composite (TFC) membranes for sustainable desalination and water reuse: A perspective - Yu Jie Lim; Kunli Goh; Naeem Nadzri; Rong Wang (Desalination, 2025)

DcNCED2 promotes ABA synthesis via carotenoid degradation and enhances drought resistance in carrot - Rong-Rong Zhang; Ya-Hui Wang; Xue-Feng Peng; Yu-Jie Sun; Nan Zhang; Ai-Sheng Xiong (Plant Cell Reports, 2025)

Phylogenomics of Paragymnopteris (Cheilanthoideae, Pteridaceae): Insights from plastome, mitochondrial, and nuclear datasets - Jing Zhao; Zhen-Long Liang; Shao-Li Fang; Rong-Juan Li; Chuan-Jie Huang; Li-Bing Zhang; Tanner Robison; Zhang-Ming Zhu; Wen-Jing Cai; Hong Yu; Zhao-Rong He; Xin-Mao Zhou (Molecular Phylogenetics and Evolution, 2025)

Accumulation of lipophilic and proteinophilic halogenated organic pollutants (HOPs) in the different types of feathers of laying hens - Xi Chen; Xiao-Jun Luo; Qun-Jie Feng; Yu Liu; Jun-Zhe Dai; Peng-Peng Chen; Pei-Xin Su; Qing-Rong Yang; Yan-Hong Zeng; Bi-Xian Mai (Journal of Hazardous Materials, 2025)

Construction of high-voltage aqueous Zn-MnO2 batteries based on polar small-molecule organic acid-induced MnO2/Mn2+ reactions - Ying Li; Nan Zhang; Jing-Yu Wang; Pengfei Wang; Zonglin Liu; Yan-Rong Zhu; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

Integrative transcriptomic analysis reveals a broad range of toxic effects of triclosan on coral Porites lutea - Hao Liang; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Rong-Gui Zhu; Chao-Yang Zhou; Zhen-Zhu Liu; Kefu Yu (Journal of Hazardous Materials, 2024)

Lattice-Engineering modulated band structure facilitates enhanced stability of high-voltage LiCoO2 at 4.6 V - Zhi Zhang; Guang-Xin Wu; Zhou-Liang Tan; He-Zhang Chen; Zhen Yu; Zhen-Rong Yu; Xiao-Bing Huang; Wen-Jie Yang; Ying-De Huang (Chemical Engineering Journal, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

Correction: Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

The CYP3A inducer dexamethasone affects the pharmacokinetics of sunitinib by accelerating its metabolism in rats - Guang-rong Lu; Rui-zhen Wang; Xin-yu Zhao; Jun-er Xu; Cheng-ke Huang; Wei Sun; Rui-jie Chen; Zhe Wang (Chemico-Biological Interactions, 2024)

A potential trade-off between reproduction and enhancement of thermotolerance in Liriomyza trifolii populations driven by thermal acclimation - Yu-Cheng Wang; Ya-Wen Chang; Fei Yang; Wei-Rong Gong; Jie Hu; Yu-Zhou Du (Journal of Thermal Biology, 2024)

The morphology of liquid CO2 hydrate films at different temperatures under saturation pressure - Yu-Jie Zhu; Yu Zhang; Yu-Zhou Chen; Yan Xie; Jin-Rong Zhong; Xiao-Hui Wang; Peng Xiao; Yi-Fei Sun; Chang-Yu Sun; Guang-Jin Chen (Chemical Engineering Journal, 2024)

Developing Estimation Equations for the Cerchar Abrasivity Index of Rocks Applicable to TBM Tunnels - Lei She; Yan-long Li; She-rong Zhang; Chao Wang; Sun-wen He; Yu-jie Wang; Ming-ming He; Sheng-le Wang (Rock Mechanics and Rock Engineering, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Rapid adsorptive removal of emerging and legacy per- and polyfluoroalkyl substances (PFASs) from water using zinc chloride-modified litchi seed-derived biochar - Zhen-Zhu Liu; Chang-Gui Pan; Feng-Jiao Peng; Jun-Jie Hu; Hong-Ming Tan; Rong-Gui Zhu; Chao-Yang Zhou; Hao Liang; Kefu Yu (Bioresource Technology, 2024)

Molecular insights into the functional analysis of P450 CYP321A7 gene in the involvement of detoxification of lambda-cyhalothrin in Spodoptera frugiperda - Wan-Ting Li; Jia-Yu Lin; Jia-Jie Liu; Muhammad Hafeez; Shi-Wen Deng; Hong-Yu Chen; Rong-Jie Ren; Muhammad Shoaib Rana; Rui-Long Wang (Pesticide Biochemistry and Physiology, 2024)

Simultaneous determination of trace marine lipophilic and hydrophilic phycotoxins in various environmental and biota matrices - Chao-Yang Zhou; Chang-Gui Pan; Feng-Jiao Peng; Rong-Gui Zhu; Jun-Jie Hu; Kefu Yu (Marine Pollution Bulletin, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Assessment of health risks associated with prediction of vegetable inorganic arsenic concentrations given different soil properties - Yi-Jie Liao; Yu-Rong Cao; Dar-Yuan Lee (Environmental Geochemistry and Health, 2024)

The environmental analysis and site selection of mussel and large yellow croaker aquaculture areas based on high resolution remote sensing - Lina Cai; Jie Yin; Xiaojun Yan; Yongdong Zhou; Rong Tang; Menghan Yu (Acta Oceanologica Sinica, 2024)

An empirical method for estimating TBM penetration rate using tunnelling specific energy - Lei She; Cheng-cheng Hu; Yan-long Li; She-rong Zhang; Chao Wang; Yu-jie Wang; Ming-ming He; Shi-min Li; Sheng-le Wang (Tunnelling and Underground Space Technology, 2024)

Developing a highly efficient, environmentally friendly and cost-effective copper sulfide semiconductor sponge for nuclear wastewater treatment under one sun - Wencai Bai; Mengjiao Liu; Kaifu Yu; Xin Cao; Jie Lian; Zhibin Zhao; Yong Xiang; Baoliang Xu; Tao Chen; Rong He; Nan Sun; Wenkun Zhu (Journal of Environmental Chemical Engineering, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Parabens and their metabolite in a marine benthic-dominated food web from the Beibu gulf, South China Sea: Occurrence, trophic transfer and health risk assessment - Rong-Gui Zhu; Chang-Gui Pan; Feng-Jiao Peng; Chao-Yang Zhou; Jun-Jie Hu; Kefu Yu (Water Research, 2024)

A novel approach to modify Stenotrophomonas sp. D6 by regulating the salt composition in the growth medium: Enhanced removal performance of Cr(VI) - Shilin Zha; Zhongbing Wang; Rong Tan; Jie Gong; Ao Yu; Tingting Liu; Chunli Liu; Chunjian Deng; Guisheng Zeng (Journal of Hazardous Materials, 2024)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Engineered hydrochar from waste reed straw for peroxymonosulfate activation to degrade quinclorac and improve solanaceae plants growth - Chunxia Ding; Can Ye; Wei Zhu; Guangyong Zeng; Xuemei Yao; Yu Ouyang; Jie Rong; Yaping Tao; Xiangying Liu; Yaocheng Deng (Journal of Environmental Management, 2023)

An airflow-driven system for scalable production of nano-microfiber wrapped triboelectric yarns for wearable applications - Yu Chen; Jie Hua; Yali Ling; Yang Liu; Mingtai Chen; Beomjun Ju; Wei Gao; Amanda Mills; Xiaoming Tao; Rong Yin (Chemical Engineering Journal, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Efficient capture of iodine by charge-induced effect of nitrogen-rich ionic liquids - Shi-Jie Guo; Guo-Hao Zhang; Qiu-Hong Zhu; Chao Yu; Jia-Ying Liu; Xiao-Lan Yang; Song Qin; Nan-Rong Zhao; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

Towards disentangling the classification of freshwater fish trypanosomes - Peng Zhang; Jie Liu; Xiao-Ming Yin; Jun-Yu Zhou; Julius Lukeš; Zhao-Rong Lun; De-Hua Lai (Marine Life Science & Technology, 2023)
Currently, new species of freshwater fish trypanosomes, which are economically important parasites, are being described based on subjectively selected features, i.e., their cell morphology and the host species. We have performed detailed phylogenetic and haplotype diversity analyses of all 18S rRNA genes available for freshwater fish trypanosomes, including the newly obtained sequences of Trypanosoma carassii and Trypanosoma danilewskyi . Based on a sequence similarity of 99.5%, we divide these trypanosomes into 15 operational taxonomic units, and propose three nominal scenarios for distinguishing T. carassii and other aquatic trypanosomes. We find evidences for the existence of a low number of freshwater fish trypanosomes, with T. carassii having the widest geographic and host ranges. Our analyses support the existence of an umbrella complex composed of T. carassii and two sister species.

Evaluating the impact of the humic acid amendment on antibiotic resistance genes reduction and product quality during swine manure composting - Yousif Abdelrahman Yousif Abdellah; Hong-Yu Chen; Shan-Shan Sun; Xi Yang; Yu-Sen Luo; Ayodeji Bello; Taha Ahmed Mohamed; Rong-Jie Ren; Wan-Ting Li; Rashid Mohamed Ahmed; Rui-Long Wang (Journal of Environmental Chemical Engineering, 2023)

The acceleration on decolorization of azo dyes by magnetic lignin-based materials via enhancing the extracellular electron transfer - Rong-ping Chen; Xin-yuan Wei; Cheng-hao Gan; Bing-cai Cai; Wen-jie Xu; Shareen Niyazi; Quan Wang; Lei Yu; Hui-hua Min; Qiang Yong (Journal of Environmental Management, 2023)

Enhancing fengycin production in the co-culture of Bacillus subtilis and Corynebacterium glutamicum by engineering proline transporter - Geng-Rong Gao; Si-Yu Wei; Ming-Zhu Ding; Zheng-Jie Hou; Dun-Ju Wang; Qiu-Man Xu; Jing-Sheng Cheng; Ying-Jin Yuan (Bioresource Technology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Endocrine-disrupting chemicals and autoimmune diseases - Rong-Gui Huang; Xian-Bao Li; Yi-Yu Wang; Hong Wu; Kai-Di Li; Xue Jin; Yu-Jie Du; Hua Wang; Fang-Yi Qian; Bao-Zhu Li (Environmental Research, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Effect of flue gas components on the removal of cadmium pollutants by transition metal-modified activated carbon: Density functional theory and thermodynamic study - Xin-Yue Zhou; Jia-Le Zhou; Rong Guo; Yin-jie Liu; Yi-fei Yu; Bing Zhang; Yang-Wen Wu; Li Zhao; Qiang Lu (Fuel, 2023)

In-depth profiling of di(2-ethylhexyl) phthalate metabolic footprints in rats using click chemistry-mass spectrometry probes - Yu-Ning Hu; Jin-Tao Zhan; Pei-Rong Bai; Na An; Jun-Jie Tan; Yan-Zhen Wang; Quan-Fei Zhu; Yu-Qi Feng (Journal of Hazardous Materials, 2023)

Phytoplankton community changes in a coastal upwelling system during the last century - Peng Peng; Rong Bi; Julian P. Sachs; Jie Shi; Yifei Luo; Weifang Chen; Chih-An Huh; Meng Yu; Yali Cao; Yaoyao Wang; Zhong Cao; Xiaohan Bao; et al. (Global and Planetary Change, 2023)

Polyphenolic-modified cellulose acetate membrane for bone regeneration through immunomodulation - Qing-Yi Zhang; Jie Tan; Kai Huang; Rong Nie; Zi-Yuan Feng; Chen-Yu Zou; Qian-Jin Li; Jun Chen; Ning Sheng; Bo-Quan Qin; Zhi-Peng Gu; Li-Min Liu; et al. (Carbohydrate Polymers, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

Effects of demineralization mode and particle size of allogeneic bone powder on its physical and chemical properties - Kun-xiu Song; Shao-lin Ji; Yong-jie Zhao; Hao-ran Zhang; Rong-xing Ma; Jing-yu Zhang; Yong-cheng Hu (Cell and Tissue Banking, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Enhanced breakdown strength and electrostatic energy density of polymer nanocomposite films realized by heterostructure ZnO-ZnS nanoparticles - Jie Liu; Linye Ji; Junyi Yu; Shanjun Ding; Suibin Luo; Baojin Chu; Jianbin Xu; Rong Sun; Shuhui Yu (Chemical Engineering Journal, 2023)

Spatiotemporal impacts of climate change and human activities on water resources and ecological sensitivity in the Mekong subregion in Cambodia - Yi Lin; Yu Rong; Lang Li; Fengting Li; Hanchao Zhang; Jie Yu (Environmental Science and Pollution Research, 2023)

A strategy for screening and identification of new amino acid-conjugated bile acids with high coverage by liquid chromatography-mass spectrometry - Yan-Zhen Wang; Peng-Cheng Mei; Pei-Rong Bai; Na An; Jin-Gang He; Jie Wang; Quan-Fei Zhu; Yu-Qi Feng (Analytica Chimica Acta, 2023)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Application of the frequency-matching method in the probability forecast of landfalling typhoon rainfall - Rong Guo; Hui Yu; Zifeng Yu; Jie Tang; Lina Bai (Frontiers of Earth Science, 2022)

Comparison of nominal and standardized catch per unit effort data in quantifying habitat suitability of skipjack tuna in the equatorial Pacific Ocean - Cheng Zhou; Yuanyuan Hu; Jie Cao; Liuxiong Xu; Xuefang Wang; Rong Wan; Yu Xiao; Jiangfeng Zhu; Hao Tang (Acta Oceanologica Sinica, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Correction to: Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Synthetic antimicrobial agents inhibit aflatoxin production - Jing Li; Qing-Qing Zhi; Jie Zhang; Xiao-Yu Yuan; Li-Hong Jia; Yu-Lin Wan; Qiu-Yun Liu; Jian-Rong Shi; Zhu-Mei He (Brazilian Journal of Microbiology, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Association between PM2.5 and mortality of stomach and colorectal cancer in Xi’an: a time-series study - Crystal Jane Ethan; Kingsley Katleho Mokoena; Yan Yu; Karabo Shale; Yameng Fan; Jie Rong; Feng Liu (Environmental Science and Pollution Research, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Impact of CYP2R1, CYP27A1 and CYP27B1 genetic polymorphisms controlling vitamin D metabolism on susceptibility to hepatitis C virus infection in a high-risk Chinese population - Jing-jing Yang; Hao-zhi Fan; Ting Tian; Meng-ping Wu; Chao-nan Xie; Peng Huang; Rong-bin Yu; Hong-Gang Yi; Yun Zhang; Jie Wang (Archives of Virology, 2019)

The effect of ambient air pollution on circulatory mortality: a short-term exposure assessment in Xi’an, China - Kingsley Katleho Mokoena; Crystal Jane Ethan; Yan Yu; Karabo Shale; Yameng Fan; Feng Liu; Jie Rong (Environmental Science and Pollution Research, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Phthalates in residential and agricultural soils from an electronic waste-polluted region in South China: distribution, compositional profile and sources - Shao-hui Zhang; Ai-jing Guo; Tong-tong Fan; Rong Zhang; Yu-jie Niu (Environmental Science and Pollution Research, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Correction to: Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji‑Dong Ya; Zhi‑Xiang Yu; Yong-Qiong Yang; Shu‑Dong Zhang; Zhi‑Rong Zhang; Jie Cai; Jun‑Bo Yang; Wen‑Bin Yu (Conservation Genetics Resources, 2018)

Complete chloroplast genome of Firmiana major (Malvaceae), a critically endangered species endemic to southwest China - Ji-Dong Ya; Zhi-Xiang Yu; Yan-Qiong Yang; Shu-Dong Zhang; Zhi-Rong Zhang; Jie Cai; Jun-Bo Yang; Wen-Bin Yu (Conservation Genetics Resources, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

Co-targeting PLK1 and mTOR induces synergistic inhibitory effects against esophageal squamous cell carcinoma - Ting-Ting Liu; Kai-Xia Yang; Jing Yu; Ying-Ya Cao; Jian-Song Ren; Jia-Jie Hao; Bei-Qing Pan; Sai Ma; Li-Yan Yang; Yan Cai; Ming-Rong Wang; Yu Zhang (Journal of Molecular Medicine, 2018)

Autophagic Modulation by Trehalose Reduces Accumulation of TDP-43 in a Cell Model of Amyotrophic Lateral Sclerosis via TFEB Activation - Ying Wang; Feng-Tao Liu; Yi-Xuan Wang; Rong-Yuan Guan; Chen Chen; Da-Ke Li; Lu-Lu Bu; Jie Song; Yu-Jie Yang; Yi Dong; Yan Chen; Jian Wang (Neurotoxicity Research, 2018)

Extension of C. elegans lifespan using the ·NO-delivery dinitrosyl iron complexes - Hsiao-Wen Huang; Yen-Hung Lin; Min-Hsuan Lin; Ya-Rong Huang; Chih-Hung Chou; Hsiao-Chin Hong; Mei-Ren Wang; Yu-Ting Tseng; Po-Chun Liao; Min-Chuan Chung; Yu-Jie Ma; Shou-Cheng Wu; et al. (JBIC Journal of Biological Inorganic Chemistry, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Effect of spatial variability of engineering properties on stability of a CSMC embankment - Rong-Jun Zhang; Mohammed Shareef M. S. Hasan; Jun-Jie Zheng; Yu-Shi Cheng (Marine Georesources & Geotechnology, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

The levels of DNGR-1 and its ligand-bearing cells were altered after human and simian immunodeficiency virus infection - Wen-Rong Yao; Dong Li; Lei Yu; Feng-Jie Wang; Hui Xing; Gui-Bo Yang (Immunologic Research, 2017)

Research on the initial allocation of carbon emission quotas: evidence from China - Yu-Jie Hu; Rong Han; Bao-Jun Tang (Natural Hazards, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The LXR ligand GW3965 inhibits Newcastle disease virus infection by affecting cholesterol homeostasis - Xiang-xiang Sheng; Ying-jie Sun; Yuan Zhan; Yu-rong Qu; Hua-xia Wang; Miao Luo; Ying Liao; Xu-sheng Qiu; Chan Ding; Hong-jie Fan; Xiang Mao (Archives of Virology, 2016)

Bridge life cycle assessment with data uncertainty - Yu-Rong Zhang; Wen-Jie Wu; Yuan-Feng Wang (The International Journal of Life Cycle Assessment, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Characteristics of gravity anomalies and prediction of volcanosedimentary boron deposit distribution in the Xiongba area, Tibet - Li-Rong Song; Chang-Qing Yu; Gui-Hua Li; Yang-Yang Feng; Jun-Jie He (Applied Geophysics, 2015)

Esthetic Management of Mucogingival Defects After Excision of Epulis Using Laterally Positioned Flaps - Yu-feng Xie; Rong Shu; Jie-lei Qian; Zhi-kai Lin; Georgios E. Romanos (Cell Biochemistry and Biophysics, 2015)

The impact of the cognition of landscape experience on tourist environmental conservation behaviors - Yu-ling Zhang; Jie Zhang; Hong-Lei Zhang; Shao-wen Cheng; Yong-rui Guo; Jin-hai Ma; Jing-rong Sun (Journal of Mountain Science, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Inhibition of acid-sensing ion channel 1a in hepatic stellate cells attenuates PDGF-induced activation of HSCs through MAPK pathway - Fan-rong Wu; Chun-xiao Pan; Chao Rong; Quan Xia; Feng-lai Yuan; Jie Tang; Xiao-yu Wang; Nan Wang; Wen-lin Ni; Fei-hu Chen (Molecular and Cellular Biochemistry, 2014)

Knockdown of LYRM1 Rescues Insulin Resistance and Mitochondrial Dysfunction Induced by FCCP in 3T3-L1 Adipocytes - Min Zhang; Zhen-Ying Qin; Yong-mei Dai; Yu-Mei Wang; Guan-zhong Zhu; Ya-Ping Zhao; Chen-Bo Ji; Jin-Gai Zhu; Chun-Mei Shi; Jie Qiu; Xin-Guo Cao; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2014)

Role of Interleukin-22 in liver diseases - Chun-xiao Pan; Jie Tang; Xiao-yu Wang; Fan-rong Wu; Jin-fang Ge; Fei-hu Chen (Inflammation Research, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

A Novel Peptide Can Mimic Extracellular Fibrinogen-Binding Protein to Block the Activation of Complement System - Ya-ping Gao; Jie Dong; Xin Zhang; Yu Liu; Qiang Lu; Jian-nan Feng; Xiao-rong Tan; Guang Yang (Cell Biochemistry and Biophysics, 2013)

Molecular and pathogenic characterization of new Xanthomonas oryzae pv. oryzae strains from the coastline region of Fangchenggang city in China - Shu-Qing Yang; Shu-Yan Liu; Shuai Zhao; Yan-Hua Yu; Rong-Bai Li; Cheng-Jie Duan; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2013)

The Implantable and Biodegradable PHBHHx 3D Scaffolds Loaded with Protein-Phospholipid Complex for Sustained Delivery of Proteins - Qiang Peng; Yong-Jie Yang; Ting Zhang; Cheng-Yu Wu; Qin Yang; Xun Sun; Tao Gong; Ling Zhang; Zhi-Rong Zhang (Pharmaceutical Research, 2013)

Influence of education and working background on physicians’ knowledge of secondary prevention guidelines for coronary heart disease: results from a survey in China - Yan-jun Gong; Tao Hong; Jie Jiang; Rong-hui Yu; Yan Zhang; Zhao-ping Liu; Yong Huo (Journal of Zhejiang University-SCIENCE B, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Validation and dissection of quantitative trait loci for leaf traits in interval RM4923-RM402 on the short arm of rice chromosome 6 - BO SHEN; WEI-DONG YU; JING-HONG DU; YE-YANG FAN; JI-RONG WU; JIE-YUN ZHUANG (Journal of Genetics, 2011)

Evaluation of the hepatoprotective and antioxidant activities of Rubus parvifolius L. - Jie Gao; Cui-rong Sun; Jie-hong Yang; Jian-mei Shi; Yue-guang Du; Yu-yan Zhang; Jin-hui Li; Hai-tong Wan (Journal of Zhejiang University-SCIENCE B, 2011)

Gene expression profiles of adipose tissue of high-fat diet-induced obese rats by cDNA microarrays - Jie Qiu; Rui Cheng; Xiao-yu Zhou; Jin-gai Zhu; Chun Zhu; Da-ni Qin; Chun-zhao Kou; Xi-rong Guo (Molecular Biology Reports, 2010)

Prognostic value of serum soluble Fas in patients with locally advanced unresectable rectal cancer receiving concurrent chemoradiotherapy - Qi-lian Liang; Zhou-yu Li; Guo-qiang Chen; Zhen-nan Lai; Bi-rong Wang; Jie Huang (Journal of Zhejiang University-SCIENCE B, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Resistin induces rat insulinoma cell RINm5F apoptosis - Chun-lin Gao; De-yu Zhao; Jie Qiu; Chun-mei Zhang; Chen-bo Ji; Xiao-hui Chen; Feng Liu; Xi-rong Guo (Molecular Biology Reports, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wen-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Molecular cloning and sequence analysis of the sisomicin biosynthetic gene cluster from Micromonospora inyoensis - Wun-Rong Hong; Mei Ge; Zhi-Hong Zeng; Li Zhu; Min-Yu Luo; Lei Shao; Dai-Jie Chen (Biotechnology Letters, 2009)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Srbl maps to mouse Chromosome 5 in a region harboring putative QTLs for plasma lipoprotein levels - Carrie L. Welch; Yu-Rong Xia; Ling-Jie Gu; Dietrich Machleder; Margarete Mehrabian; Ping-Zi Wen; Nancy Webb; Willem J. S. de Villiers; Deneys van der Westhuyzen; Aidons J. Lusis (Mammalian Genome, 1997)

Activation of Signal Transduction Kinases by Tamoxifen - Jauh-Lin Duh; Rong Yu; Jie-Jun Jiao; George A. Matwyshyn; Wei Li; Tse-Hua Tan; A.-N. Tony Kong (Pharmaceutical Research, 1997)